2014
DOI: 10.14327/iscm.8.1
|View full text |Cite
|
Sign up to set email alerts
|

<b>Structural Equation Modelling of Human Factors and Their Impact On </b><b>Productivity of Cellular Manufacturing </b>

Abstract: Cellular manufacturing has become an integral part of lean manufacturing systems; more and more attentions have been paid to cellular manufacturing. Although the quality and productivity of cell production systems depends largely on operators skill and other human factors, it is still insufficient to investigate how human factors affect manufacturing cells. Here, we apply structural equation modeling to analyze the impact of human factors on productivity of cellular manufacturing. We design a laboratory experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In our previous studies [5], [6], we have shown that both the experience (learning effect) and workers have significant impacts on the productivity of production cells, the impact of the experience and workers on the productivity of production cells account for 19.63% and 67.01% of the total variance in assembly times respectively. As two-thirds of variance of the assembly times were decided by workers, the aptitude or ability of workers has a stronger impact than the experience.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [5], [6], we have shown that both the experience (learning effect) and workers have significant impacts on the productivity of production cells, the impact of the experience and workers on the productivity of production cells account for 19.63% and 67.01% of the total variance in assembly times respectively. As two-thirds of variance of the assembly times were decided by workers, the aptitude or ability of workers has a stronger impact than the experience.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized that most of the problems faced by companies implementing cells were related to people, not technical issues. In our previous studies [5]- [6], it has been clarified that both the experience (learning effect) and workers have significant impacts on the productivity of production cells, the impact of the experience and workers on the productivity of production cells are 19.63% and 67.01% respectively. As two-thirds of variance of the assembly times was decided by workers, the aptitude or ability of workers has a stronger impact than the experience.…”
mentioning
confidence: 99%